Successful Treatment of Opioid Dependence with Flexible Doses of Injectable Prolonged Release Buprenorphine - Oscar D’Agnone (Case Reports in Psychiatry)
Opioid dependence (OD) may be effectively treated with well-evidenced regimens including psychosocial and pharmacotherapeutic interventions. Treatment has benefits but also limitations including risk of diversion, impact of mandatory daily supervision, and stigma. An injectable prolonged release buprenorphine with flexible dose options has recently been approved by the European Commission and is available in the UK and other European Countries. Initial positive treatment experience in patients with different clinical scenarios (patients with no recent treatment history, a transfer from oral methadone, and change from sublingual buprenorphine tablets) provides evidence of the potential benefit in a range of situations for this therapeutic option. Adoption of the injectable form was clinically successful with no withdrawal signs, nor evidence of use of other drugs. Patient reported outcomes were positive including reduction in cravings and anxiety and improved attitude, relationships, and general mood.